Replacing Corn and Wheat in Layer Diets with Hulless Oats Shows Effects on Sensory Properties and Yolk Quality of Eggs - Winkler, Louisa R.; Hasenbeck, Aimee; Murphy, Kevin M.; Hermes, James C. (Frontiers in Nutrition, 2017)
US organic poultry producers are under pressure to find feed alternatives to corn and wheat. Hulless oats offer advantages such as wide geographic adaptation of the plant and high concentrations of protein and oil in the grain. They have shown considerable potential in experimental work as a feed grain for poultry, but more research is needed into their influence on the sensory and nutritional properties of eggs. In this study, hulless oats were substituted for corn or wheat at 200g kg-1 in diets fed to Hy-Line Brown hens, and eggs were sampled for sensory evaluation after eight weeks. Discrimination tests of blended and baked egg samples found evidence of difference between eggs from oat-based diets and those from the oat-free control (p<0.05 for eggs from an oat-corn diet, p<0.01 for eggs from an oat-wheat diet). Acceptance tests of similar samples showed that eggs from the oat-wheat diet were significantly less liked than control eggs for their texture (p<0.01) and response to cooking (p<0.01), while eggs from the oat-corn diet were somewhat less liked. Yolk weight was greater (p<0.05) in Control eggs (34.1g) than eggs from oat-corn (31.6g) or oat-wheat (31.2g) diets, leading to smaller yolk proportion in the oat-fed eggs. Fatty acid profile differences across treatments were not of nutritional significance, and no evidence was found that the feeding of hulless oats improved storage properties of eggs. In this study, modifying the carbohydrate source in layer diets was shown to change textural properties of cooked eggs in a way that was perceptible to untrained consumers, probably by reducing the yolk proportion. This finding was not commercially relevant owing to small effect size, and results overall add to existing evidence that hulless oats can be fed to poultry at a moderate proportion of the diet with no negative effect on consumer acceptability of eggs. Regardless of the small effect size, however, findings are interesting from the food chemistry perspective because they provide novel evidence of how the thermal properties of eggs can be altered by a change in hen dietary carbohydrate source.